Food Taboos And Perineal Wound Healing Duration In Postpartum Mothers In The Working Area Of UPTD Non-Inpatient Public Health Center Totokaton, Batu Putih District, West Tulang Bawang Regency - Yulinda Hervilia; Yunita Anggriani; Siti Rohani; Inggit Primadevi (Sean Institute, 2024)
Healing of perineal wounds is influenced by several factors including culture of abstinence, nutrition, age, infrastructure, medicines, heredity. In this case, the culture of abstinence during the postpartum period is still being practiced, post- partum mothers who abstain from eating will avoid consuming fishy-smelling pro- teins such as: meat, eggs, fish, shrimp, crab, squid. So, in postpartum mothers who abstain from eating, the speed of healing of perineal wounds tends to be slow, and can cause infection during the postpartum period. The aim of the research is to determine the relationship between food abstinence and the length of healing of perineal wounds in postpartum mothers in the Totokaton non-inpatient health cen- ter UPTD working area. This research uses a cross sectional design, the sampling technique uses incidental sampling. The research subjects were postpartum mothers on the 7th day who experienced second degree perineal rupture in the Totokaton Non-Inpatient Health Center UPTD working area. Data collection used a questionnaire. Research analysis used the Pearson Chi Square statistical test. The research was conducted in August 2024. The research results showed that of the 46 respondents, 30 postpartum mothers (65.5%) who abstained from food experienced slow healing of perineal wounds. After carrying out the chi square test, the result was p = 0.048, meaning a relationship between food abstinence and perineal wound healing. It is hoped that postpartum mothers will consume better nutrition by not abstaining from food, the better the perineal wound healing will be.